Food Science and Technology Information Services (FOSTIS): Users Assessment of CFTRI Documentation Services - Sangameswaran, S. V.; Gopinath, M. V. (Journal of Information and Knowledge, 1977)
Discusses the scope of FOSTIS (Food Science and Technology Information Services) and its output service to users. Presents the objective, methodology, and User population of a survey of users of these services in India. The findings of the survey emphasises the value of these services to User population and the continuing need for such services in the field of food science and technology.